Agar-Based Disk Diffusion Assay for Susceptibility Testing of Dermatophytes - Nweze, E. I. (American Society for Microbiology (ASM), 2010)
Currently, no agar-based susceptibility testing method has been standardized for testing dermatophytes. We describe a newly developed agar-based method employing disk diffusion assay to test the susceptibility of 47 isolates of dermatophytes against 8 antifungals. Our results show that the method is reproducible, is simple, and could be used to determine the antifungal susceptibility of dermatophytes.